Dynamics of the atmosphere : - Zdunkowski, Wilford (Cambridge University Press, 2003)
Complete with numerous exercise sets and solutions, this work is written for advanced students of meteorology and related sciences as well as professional meteorologists and researchers. The first part of the book presents the mathematical tools needed for a thorough understanding of the topics covered in the second. These topics include kinematics of the atmosphere; inertial and dynamic stability; turbulent systems; and novel weather prediction methods with potential for extending the forecasting range.